Polarization Switching in Long-Wavelength VCSELs Subject to Orthogonal Optical Injection - Torre, M; Hurtado, A; Quirce, A; Valle, A; Pesquera, L; Adams, M (IEEE journal of quantum electronics, 2011)
Polarization switching (PS) appearing in long-wavelength vertical-cavity surface-emitting lasers (VCSELs) subject to orthogonal optical injection is investigated theoretically and experimentally. We have studied the injected optical power required for PS as a function of the frequency detuning between the injected light and the orthogonal linear polarization of the VCSEL. For a wide range of bias currents applied to the device, the injected power required for the occurrence of PS exhibited a minimum and a plateau with respect to the frequency detuning. The minimum (plateau) was found at negative (positive) frequency detuning. The bistable behavior of the polarization is described. Our experimental results confirm the theoretical predictions of Sciamanna and Panajotov. The levels of the minimum and the plateau were observed to increase as higher bias currents were applied to the VCSEL. A first theoretical and experimental observation of the disappearance and further appearance of PS when increasing the injected power in long-wavelength VCSELs is described. This situation is obtained for small levels of negative frequency detuning and for large enough values of applied bias current. A good overall qualitative agreement is found between our theoretical and experimental results.